Global cassava starch markets current situation and outlook - Henry, Guy; Westby, Andrew (International Center for Tropical Agriculture, 2001)
Current global starch production is approximating 50 million tonnes. While the starch production growth rate steadily continues to surpass average population growth figures, the make-up by starch source and production regions have been changing. The world share of cassava-based starches may range between 4-6%. While Southeast Asia continues to lead as the foremost cassava starch production (and utilization) region, both within this region and in other continents the cassava starch industry and market patterns are changing. Starting in the late 1980s and accelerating during the 90s, Latin-American and (to a minor extent) African cassava starch processing has expanded. It is most likely that this basic trend will continue into the beginning of the 21st century. However, the new century brings with it both new threats as well as additional opportunities that will greatly impact on the competitiveness of cassava as a major starch source. The paper firstly summarizes the principal global trends of starch production, utilization and markets, paying special attention to the role of cassava. In addition, individual starch regions (US, EU, Asia) and their main players will be discussed. Secondly, the foremost global and regional technical, political and economic conditions that are currently coming about will be reviewed concerning their potential impact on global starch markets. Thirdly, a synthesis is formulated as to what the most probable implications are for cassava sector researchers and developers.